Productivity increases through the implementation of a service management model based on Lean Service, MRP, and SLP in cleaning and pet care services SMEs - Calmet Olivos, Leonardo (2022)
Research on implementing work standardization in an SME company in the veterinary sector is very scarce. This scientific article aims to increase productivity without neglecting the grooming service's quality and applying different engineering solutions to improve resource management. The results obtained can be of great value to similar industries, especially those that want to improve the performance of their operations, avoid waste, and improve their productivity. In companies such as a veterinary clinic, it is common to find that those in charge of the bathroom area do not perform an outstanding performance in their work, considering this task as not very important or definitive for the company, causing unnecessary delays, slow work speed, and unmotivated staff. We seek through this article to demonstrate that, through standardization of processes and areas within a company, the imperfections found can be significantly improved with a meager investment of money. This article refers to the implementation of the standardization of work in a veterinary clinic, achieving an increase of more than 30% in its productivity.